(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2014)
Introduction. Resonance spectral filtration has an exceptional importance for many applica-tions. Resonators based on reflectors with antiphase reflection coefficients — two-phase res-onators — are proposed. Single-phase and two-phase resonators. Impedance dependencies of single- and two-phase crystal-like structures and single- and two-phase resonators are examined. Frequency de-pendences of the transmission coefficient for the single- and two-phase resonators are shown. Amplitude- and phase-frequency characteristics of resonators reflectors.The amplitude-frequency and phase-frequency characteristics of resonators reflectors are given. Coming from the condition of phases balance for a two-phase resonator reason of dis-placement of its transmission coefficient characteristic is set. Two-phase resonator structure correction. The correction of two-phase resonator structure is offered for correction of transmission coefficient characteristic displacement. Exact and ap-proximate dependencies of relative magnitude of resonant cavity length correction from the impedance are shown. Conclusions. Two-phase resonator structures are provided the increase of quality factor in comparing to the traditional single-phase structures. At the set sizes and range of impedances with the increase of impedance of layers from 3 to 10 two-phase resonator quality factor in 1.25…3 times more than single-phase resonator one.